Sabda Allah Yang Menjadi Manusia: Doktrin Kristiani dan Islam Tentang Pewahyuan. Sebuah Studi Teologi Komparatif - Prasetyantha, Y.B. (Jurnal Orientasi Baru, 2006)
Comparative theology is a new theological approach to religious plurality. It begins with taking and accepting religious diversity seriously, not as a threat but as a blessing in the deepest sense of the word. Beyond tolerance, comparative theology goes further to respond innovatively to the enormous opportunity that religious plurality offers to us to think about our own religious tradition in new ways. In fact, using a posteriori knowledge and appreciation of Muslim beliefs of the Qu'ran as revelation, in this study we have the insights to re-think and deepen our understanding of God's self-manifestation in Jesus Christ. Moreover, unexpectedly but happily we find that it is God's self-emptying love in the crucified but risen Christ which constitutes, for us, the universal criterion in regard to salvation and revelation and, at the same time, the deepest aspiration in encountering others.